Workplace Inhalant Abuse in Adult Female: Brief Report - Verma, Rohit; Balhara, Yatan Pal Singh; Deshpande, Smita N. (Case Reports in Psychiatry, 2011)
Inhalant abuse is the purposeful inhalation of intoxicating gases and vapors for the purpose of achieving an altered mental state. With its propensity for being yet an under-recognized form of substance use, being gateway to hard substances, cross-cultural penetration crossing socioeconomic boundaries, and causing significant morbidity and mortality in early ages, the prevention of inhalant misuse is a highly pertinent issue. This clinical report identifies a newer perspective in the emergence of inhalant abuse initiation. We report a case of an adult female with late onset of inhalant dependence developing at workplace and recommend for greater awareness, prevention, and management of this expanding substance abuse problem.